Historic Spatial Inequality and Poverty along Racial Lines in South Africa - Shahaboonin, Faraaz; David, Oladipo Olalekan; Wyk, Abigail Van (International Journal of Economics and Financial Issues, 2023)
South Africa faces many socio-economic challenges, which include sluggish economic growth, increasing unemployment rates, increasing inequality, and high poverty levels., This paper focused on examining how spatial inequality causes these socio-economic issues. The main thrust of the paper is to briefly investigate two major aspects, firstly the root cause of spatial inequality in South Africa, and secondly the impact that spatial inequality has on socio-economic indicators such as economic inequality, poverty, and employment levels. This research used a mixed methodology approach. Empirical research findings proved that apartheid policies contributed to high levels of poverty and inequality in South Africa. As the empirical results show, the existing inequalities in South Africa are predominantly based on a racial sub-group basis, which confirms the causal relationship with historic apartheid spatial policies enforced on a racial basis. Primary research findings depicted that the post-apartheid era is characterised by high poverty levels and huge inequality with the bulk of blacks exposed to diverse macro-economic challenges. Policy recommendation-wise, it was suggested that the government should continue to redress the systems of apartheid and use policies that help to eradicate poverty.